Is there a link between open‐angle glaucoma and dementia?. Issue 2 (10th September 2013) - Helmer, Catherine; Malet, Florence; Rougier, Marie‐Bénédicte; Schweitzer, Cédric; Colin, Joseph; Delyfer, Marie‐Noëlle; Korobelnik, Jean‐François; Barberger‐Gateau, Pascale; Dartigues, Jean‐François; Delcourt, Cécile
<x xml:space="preserve">Abstract</x> Objective Previous research has suggested an association between dementia and glaucoma through common risk factors or mechanisms. Our aim was to evaluate the longitudinal relationship between open‐angle glaucoma (OAG) and incident dementia. Methods The Three‐City–Bordeaux–Alienor study is a population‐based cohort of 812 participants with a 3‐year follow‐up period. All participants were aged 72 years or older. An eye examination was performed on all subjects. An OAG was determined based on optic nerve damage and visual field loss. Incident dementia was actively screened for and confirmed by a neurologist. Results A total of 41 participants developed dementia over the 3‐year follow‐up period. Future incident dementia cases had an increased prevalence of OAG (17.5% vs 4.5% for nondemented participants, p = 0.003). After adjustment for age, gender, education, family history of glaucoma, vascular comorbidities, and apolipoprotein ε4, our results showed that participants with an OAG were four times more likely to develop dementia during the 3‐year follow‐up period (odds ratio = 3.9, 95% confidence interval = 1.5–10.4, p = 0.0054). An increased risk of dementia was also associated with 2 markers of optic nerve degeneration (vertical cup:disk ratio and minimal rim:disk ratio). However, no association was found between a high intraocular pressure and/or the use of intraocular pressure‐lowering medications and incident dementia. Interpretation If the association between OAG and dementia is confirmed, direct and noninvasive quantification of the amount of retinal ganglion cell axonal loss may be a useful biomarker of cerebral axonal loss in the future. It may also offer new breakthroughs in understanding the underlying pathophysiological mechanisms of both diseases.